Gene Transfer to Ocular Stem Cells by Early Gestational Intraamniotic Injection of Lentiviral Vector - Endo, Masayuki; Zoltick, Philip W; Chung, Daniel C; Bennett, Jean; Radu, Antoneta; Muvarak, Nidal; Flake, Alan W (Molecular therapy, 2007)
Ocular gene transfer has generally been approached by direct intraocular injection. In this study, we hypothesized that an opportunity exists during early gestation when specific ocular stem cell populations are accessible for gene transfer. These include the stem cell populations that maintain the cornea, lens, and retina throughout life. To test this hypothesis, we injected lentiviral vector encoding the green fluorescent protein (GFP) reporter gene into the murine amniotic space from the late head fold/early somite stage postcoital day 8 (E8) to E18 and performed sequential analysis of GFP expression in ocular tissues. Depending on the timing of vector exposure, significant GFP expression was observed in all ectoderm-derived tissues in the eye. With injection at early gestational time points, GFP expression persisted long term, with evidence of high efficiency stem cell transduction in the cornea, lens, and retina. The observed patterns and duration of gene expression confirm the accessibility of ocular stem cell populations for lentiviral vector-based gene transfer at specific developmental time points in early gestation. This model may be useful for the investigation of mechanisms of genetic and/or developmental ocular disease and for the development of prenatal gene therapy for specific ocular disorders.